Beyond Labels: Can Biomarkers and Treatable Traits Revolutionize Interstitial Lung Disease Care? - Amati, Francesco; Stainer, Anna; Aliberti, Stefano (Biomedicines, 2025)
The classification of interstitial lung disease (ILD)s has traditionally relied on well-defined diagnostic labels, such as idiopathic pulmonary fibrosis (IPF), nonspecific interstitial pneumonia (NSIP), and hypersensitivity pneumonitis (HP) [...]